Features of construction of the training process of young female weightlifters of 14-15 years old in basic mesocycle of the preparatory period of the annual macrocycle taking into account specific biological cycles - Lydmila Kanunova; Oleksandr Piven (Kharkiv State Academy of Physical Culture, 2020)
Purpose: to consider the issue of the peculiarities of construction the training process of young weightlifters 14-15 years old in the basic mesocycle of the preparatory period in the annual macrocycle, taking into account the peculiarities of a specific biological cycle. Material and methods: the work uses the methods of theoretical analysis and generalization of scientific information, system analysis. The study involved young pupils of the Children and Youth Sports School No 16 and Children and Youth Sports School No 8, Kharkov. The experiment involved 24 young female weightlifters 14-15 years old, who were divided into two groups: control and experimental, 12 athletes in each group. The participants in the experiment trained 3-4 times a week in accordance with the developed methodology. Results: presents modern approaches to the peculiarities of building the training process of young weight-lifters 14-15 years old; provides a detailed structure for constructing the basic mesocycle in the annual macrocycle, taking into account the phases of the ovarian-menstrual cycle. Comparative analysis of indicators of special exercises and general physical fitness of female athletes in the control and experimental groups at the beginning and at the end of the experiment showed that the level of general physical fitness of athletes in the experimental group significantly increased under the influence of the proposed methodology. Conclusions: it was determined that among young athletes involved in kettlebell lifting it is necessary in the basic mesocycle of the annual macrocycle to carry out the distribution of loads in accordance with the phases of the ovarian-menstrual cycle. The introduction of the methodology of the training process of young kettlebells 14-15 years old in the basic mesocycle of the annual macrocycle, taking into account the phases of the ovarian-menstrual cycle, contributed to a significant increase in the indicators of general and special-auxiliary exercises in the experimental group.